Digital image processing algorithms and applications 2026-02-15T20:26:54+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Pitas, I. (Ioannis) ) (Wiley, 2000)

(untitled)
"The author guides readers through all facets of the technology, supplementing the discussion with detailed lab exercises in EIKONA, his own digital image processing software, as well as useful PDF transparencies. He covers in depth filtering and enhancement, transforms, compression, edge detection, region segmentation, and shape analysis, explaining at every step the relevant theory, algorithm structure, and its use for problem solving in various applications. The availability of the lab exercises and the source code (all algorithms are presented in C-code) over the Internet makes the book an invaluable self-study guide